2001
DOI: 10.1021/jo016101c
|View full text |Cite
|
Sign up to set email alerts
|

Motuporamines, Anti-Invasion and Anti-Angiogenic Alkaloids from the Marine Sponge Xestospongia exigua (Kirkpatrick):  Isolation, Structure Elucidation, Analogue Synthesis, and Conformational Analysis

Abstract: Extracts of the sponge Xestospongia exigua collected in Papua New Guinea were positive in a new assay for anti-invasion activity. Bioassay-guided fractionation led to the identification of the three known motuporamines A (1), B (2), and C (3) along with the new motuporamines D (4), E (5), and F (6) and a mixture of G, H, and I (15). Motuporamines A (1), B (2), and C (3) and the mixture of G, H, and I (15) were responsible for the anti-invasion activity of the crude extract. Motuporamine C (3) has also been fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 22 publications
2
65
0
Order By: Relevance
“…Eight motuporamines including motuporamine A (36), B (37) and C (38) , D(39), E (40) and F (41) and a mixture of G, H, and I (42) were obtained from N. exigua (Xestospongia exigua) collected from Papua New Guinea yielded (Williams et al, 1998;Williams et al, 2002). Two phenethyl-guanidine derivatives, 7,8-dihydrotubastrine (43) and 4-deoxy-7,8-dihydrotubastrine (44), were isolated from the from the Indo-Pacific sponge N. contignata (Petrosia cf.…”
Section: Others Alkaloidsmentioning
confidence: 99%
“…Eight motuporamines including motuporamine A (36), B (37) and C (38) , D(39), E (40) and F (41) and a mixture of G, H, and I (42) were obtained from N. exigua (Xestospongia exigua) collected from Papua New Guinea yielded (Williams et al, 1998;Williams et al, 2002). Two phenethyl-guanidine derivatives, 7,8-dihydrotubastrine (43) and 4-deoxy-7,8-dihydrotubastrine (44), were isolated from the from the Indo-Pacific sponge N. contignata (Petrosia cf.…”
Section: Others Alkaloidsmentioning
confidence: 99%
“…Using a three-step screening assay for inhibitors of tumor cell invasion, motuporamines A, B, C, and an unresolved mixture of motuporamines G, H, and I, were isolated from the marine sponge Xestospongia exigua and found to inhibit the invasion of tumor cells into basement membranes [31,32]. The structures of the motuporamines are shown in Fig.…”
Section: Angiogenesismentioning
confidence: 99%
“…In addition to inhibiting tumor cell invasion, the most potent compound, motuporamine C also inhibits endothelial sprout formation in vitro (complete inhibition at 10 μM) and angiogenesis in vivo (CAM assay with 30 ng/mL VEGF stimulated angiogenesis, complete inhibition at 10 μM). Structure-activity studies on a series of natural and synthetic motuporamine analogues revealed that the maximum anti-invasion activity of this alkaloid family requires a saturated monocyclic amine with a ring size of 13, 14, or 15, fused to a linear side chain with two basic nitrogen atoms, each separated by three methylene carbons [32].…”
Section: Angiogenesismentioning
confidence: 99%
“…Sponges are utilized as therapeutic agents. A literature search revealed that few compounds have been reported from S. officinalis, including alkaloids and steroids (Lin et al, 2003;Lin et al, 2001;Thale et al, 2002;Orabi et al, 2002;Edrada et al, 2002;Williams et al, 2002;Bohlin et al, 1980).…”
Section: Introductionmentioning
confidence: 99%